Optimizing Educational Facilities and Infrastructure in the Context of Marketing Management - Ramadhania, Yaya; Nurmaliah, Nurmaliah; Nelinda, Afneli; Kasmah, Kasmah (DIDAKTIKA, 2023)
This study explores the strategic role of facilities and infrastructure optimization in enhancing educational marketing management at SMAN 30 Bone, Indonesia. The research addresses a critical gap in the alignment between physical resources and institutional promotional efforts in secondary education. Employing a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and document analysis involving school leaders, teachers, and students. Findings reveal that while the school has implemented relatively effective marketing strategies, the lack of adequate learning facilities and basic infrastructure such as laboratory tools, sports equipment, and religious spaces poses challenges to achieving educational excellence and stakeholder satisfaction. The optimization of both facilities and infrastructure was found to directly influence parents’ and students’ perceptions of educational quality, which in turn affected enrollment decisions. This study contributes to the discourse on education service marketing by highlighting the interdependence between infrastructure development and institutional image-building. The implications underscore the need for integrated planning in resource allocation, particularly for newly established schools seeking to strengthen their competitive positioning. The findings are relevant for policymakers, school administrators, and education planners aiming to enhance school attractiveness and community trust through strategic infrastructure investment.